2008
DOI: 10.1208/s12249-008-9124-y
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Percutaneous Permeation and Skin Accumulation of Finasteride Using Vesicular Ethosomal Carriers

Abstract: Abstract. In order to develop a novel transdermal drug delivery system that facilitates the skin permeation of finasteride encapsulated in novel lipid-based vesicular carriers (ethosomes)finasteride ethosomes were constructed and the morphological characteristics were studied by transmission electron microscopy. The particle size, zeta potential and the entrapment capacity of ethosome were also determined. In contrast to liposomes ethosomes were of more condensed vesicular structure and they were found to be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 22 publications
0
45
0
5
Order By: Relevance
“…Ethosomes and liposomes were prepared and characterized as previously described (Rao et al, 2008). The SPL (3% w/w) and drug (0.2% w/w) were dissolved in ethanol in a sealed glass container, and then the water was added slowly in a constant stirring condition, keeping in mixing for 5 min.…”
Section: Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Ethosomes and liposomes were prepared and characterized as previously described (Rao et al, 2008). The SPL (3% w/w) and drug (0.2% w/w) were dissolved in ethanol in a sealed glass container, and then the water was added slowly in a constant stirring condition, keeping in mixing for 5 min.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The film was dispersed with water and completely hydrated. The final sample was processed with the method described in ethosomes preparation (Rao et al, 2008). Each time 20 mg drug was used for the preparation of 10 g formulation.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several studies which showed that topical application of the drug might be better option to avoid the unwanted side effects encountered when orally administered (Tabbakhian et al, 2006;Kumar et al, 2007). Specifi cally, since the target tissue of FNS for the treatment of androgenetic alopecia is hair follicles in the scalp, various topical formulation of the drug was pursued using liposomes, ethosomes, niosomes, solid lipid nanoparticles, and nanostructured lipid carriers (Biruss and Valenta, 2006;Biruss et al, 2007;Rao et al, 2008;Balakrishnan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%